ZW10 helps recruit dynactin and dynein to the kinetochore. - Starr, D.A.; Williams, B.C.; Hays, T.S.; Goldberg, M.L. (Journal of Cell Biology, 1998)
Mutations in the Drosophila melanogaster zw10 gene, which encodes a conserved, essential kinetochore component, abolish the ability of dynein to localize to kinetochores. Several similarities between the behavior of ZW10 protein and dynein further support a role for ZW10 in the recruitment of dynein to the kinetochore: (a) in response to bipolar tension across the chromosomes, both proteins mostly leave the kinetochore at metaphase, when their association with the spindle becomes apparent; (b) ZW10 and dynein both bind to functional neocentromeres of structurally acentric minichromosomes; and (c) the localization of both ZW10 and dynein to the kinetochore is abolished in cells mutant for the gene rough deal. ZW10's role in the recruitment of dynein to the kinetochore is likely to be reasonably direct, because dynamitin, the p50 subunit of the dynactin complex, interacts with ZW10 in a yeast two-hybrid screen. Since in zw10 mutants no defects in chromosome behavior are observed before anaphase onset, our results suggest that dynein at the kinetochore is essential for neither microtubule capture nor congression to the metaphase plate. Instead, dynein's role at the kinetochore is more likely to be involved in the coordination of chromosome separation and/or poleward movement at anaphase onset.